The Zoonotic Disease Human Monkey Pox: An Insights into Epidemiological, Clinical, and Preventative Features - Raheela Bano, Muhammad Jamil, Muhammad Kashif, Muhammad Qasim, Muqadas Khan, Mubarik Ali, Norina Jabeen, Sajad Ahmad, Rida Naz, (Pakistan Journal of Medical & Health Sciences, 2022)
Monkeypox is no longer "an uncommon viral zoonotic disease" because it has spread all over the world and the outbreak is still occurring. It is concerning that the disease has spread to other regions and countries. There is a lack of information regarding the ecological, zoonotic, epidemiologic, clinical, and public health aspects of monkeypox. Significant adverse effects are associated with the first-generation live attenuated vaccinia virus vaccinations that are stored for use in emergency situations in multiple countries. As a result of the cessation of smallpox vaccinations, an ecological void has been created in which more people have diminished or no protection against MPXV. This will increase the rate of virus transmission from animals to humans as well as from humans to other humans. Urgent research and monitoring should be carried out as part of a global initiative titled "One-Human-Animal Environmental Health."